1987
DOI: 10.1021/jo00229a037
|View full text |Cite
|
Sign up to set email alerts
|

Convenient synthesis of 2-halo-2'-deoxyadenosines

Abstract: on a column of silica gel (eluting solvent: benzene). The first materia] to emerge from the column was the desired 2,8,17-trithia [45,12] [9]metacyclophane, which was recrystallized from ethyl acetate (85 mg, 0.27 mmol, 5.5% yield). The melting behavior was unusual: at 170-180 °C, the crystals softened and bent, but did not liquefy; at 280 °C the material began to discolor; decomposition was gradual from 300-350 °C (lit.1 2mp 176 °C). lH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…A search of the literature found that N 2 -aryl-2-aminopurine derivatives had been synthesized by the reaction of 2-bromopurines with the appropriate aromatic amine in alcohol at reflux. , This result indicated that direct displacement of bromide from the purine C2 could be accomplished with weak nucleophiles, such as aromatic amines. In addition, it was found that 2-halo-6-bromopurine derivatives underwent substitution at the C6 position under mild conditions (25 °C), whereas, the subsequent reaction at the C2 position required more forcing conditions (120 °C) . Little was known, however, regarding the efficiency of direct displacement of bromide from the 6-position of 6-bromopurine nucleosides.…”
Section: Resultsmentioning
confidence: 99%
“…A search of the literature found that N 2 -aryl-2-aminopurine derivatives had been synthesized by the reaction of 2-bromopurines with the appropriate aromatic amine in alcohol at reflux. , This result indicated that direct displacement of bromide from the purine C2 could be accomplished with weak nucleophiles, such as aromatic amines. In addition, it was found that 2-halo-6-bromopurine derivatives underwent substitution at the C6 position under mild conditions (25 °C), whereas, the subsequent reaction at the C2 position required more forcing conditions (120 °C) . Little was known, however, regarding the efficiency of direct displacement of bromide from the 6-position of 6-bromopurine nucleosides.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, l a was prepared from 2-iodoadenosine photochemically [ 191. We observed that the very potent antileucemic drug [20] 2-chloro-2'-deoxyadenosine (9a) prepared from dichloro compound 8a [21[ [22] as well as its bromo analogue 10 [23] also underwent photochemical transformation. As we considered the syntheses of the base-modified 2'-deoxyisoguanosine analogues 3 and 4, we tested the applicability of this reaction on compounds 9b [24], and pyrazolo[3,4-d]pyrimidine derivative 9c was obtained from 8c [25] by selective displacement of the 4-chloro substituent with methanolic ammonia under simultaneous deprotection of the toluoyl groups (Scheme 2).…”
Section: Aa)mentioning
confidence: 99%
“…The efficient chemical method for the synthesis of cladribine consists in the stereospecific glycosylation of sodium salt of 2,6-dichloropurine with 2-deoxy-3,5-di-O-p-toluoyl-a-d-ribofuranosyl chloride leading to the formation of the corresponding N 9 -b-d-nucleoside as the main product (58%), along with the N 9 -a-d-isomer (13%) [31] [32]. Treatment of the former with NH 3 afforded cladribine (71%) [31] [32].…”
mentioning
confidence: 99%
“…Treatment of the former with NH 3 afforded cladribine (71%) [31] [32]. Two enzymatic approaches have been used for the preparation of cladribine.…”
mentioning
confidence: 99%